(untitled) (Italiano LinguaDue, 2023)
L’intervento analizza alcune scelte testuali di Paolo Conte in relazione all’annosa questione dell’italiano come lingua difficile da gestire in simbiosi con l’accompagnamento musicale: problema denunciato in più riprese dagli addetti ai lavori, che hanno evidenziato come la mancanza di un adeguato repertorio di parole tronche nella nostra lingua renda spesso problematica la gestione della struttura metrica del testo cantato. Between style and necessity. On language and metrics in paolo conte and the italian songwriting The essay analyzes some textual choices by Paolo Conte in relation to the age-old question of Italian as a language difficult to manage in symbiosis with musical accompaniment: a problem denounced on several occasions by songwriters and lyricists, who have highlighted how the absence of a adequate repertoire of oxytone words in Italian language often involves difficulties in managing the metric structure of lyrics in music.